Awake intubation with videolaryngoscopy and fiberoptic bronchoscope. Issue 1 (11th January 2022) - Utada, Shusuke; Okano, Hiromu; Miyazaki, Hiroshi; Niida, Shoko; Horiuchi, Hiroshi; Suzuki, Naoya; Otsuka, Tsuyoshi; Furuya, Ryosuke
Abstract: By combining video laryngoscopy and fiberoptic bronchoscopy, awake intubation can be performed more safely. Abstract : The simultaneous display of bronchoscope and laryngoscope images on a single screen allows for safer conscious tracheal intubations.